The only hope for America: the transforming power of the Gospel of Jesus Christ - Palau, Luis (Crossway Books, 1996)
The church's (forgotten) number one priority -- Changing America from the inside out -- A message for America -- The gospel of reconciliation -- Who's telling the gospel truth? -- Good works aren't good enough -- The future of crusade evangelism -- God's obsession -- Nailed by the gospel -- Dream great dreams